Interrater Agreement on the Visual Analysis of Individual Tiers and Functional Relations in Multiple Baseline Designs. (November 2016) - Wolfe, Katie; Seaman, Michael A.; Drasgow, Erik
Previous research on visual analysis has reported low levels of interrater agreement. However, many of these studies have methodological limitations (e.g., use of AB designs, undefined judgment task) that may have negatively influenced agreement. Our primary purpose was to evaluate whether agreement would be higher than previously reported if we addressed these weaknesses. Our secondary purposes were to investigate agreement at the tier level (i.e., the AB comparison) and at the functional relation level in multiple baseline designs and to examine the relationship between raters' decisions at each of these levels. We asked experts ( N = 52) to make judgments about changes in the dependent variable in individual tiers and about the presence of an overall functional relation in 31 multiple baseline graphs. Our results indicate that interrater agreement was just at or just below minimally adequate levels for both types of decisions and that agreement at the individual tier level often resulted in agreement about the overall functional relation. We report additional findings and discuss implications for practice and future research.